Through the Words of a Poet: Experiencing a Writing Journey (LEARNing Landscapes, 2010)
My PhD dissertation (Guiney Yallop, 2008) is an arts-based, autoethnographic, queer study. I wrote poetry to generate the data for my research.The first section of my dissertation consists of 46 poems, the first 23 of which are my Catholic terrain and the other 23 are my Education terrain.The poems are followed by an exegesis divided into 12 pauses. This article comes from the fifth pause where I explained the process I engaged in while writing the poetry and when I was putting the poems together in my dissertation. While each writer has her or his own processes when writing, I believe that making our processes explicit allows us and our readers to more fully appreciate how we construct our writing. As well as reflecting on the process, the reader may consider the content and the form of the writing; what are the poems saying and how are they saying it?
Keywords: arts-based; autoethnography; queer; poetry; writing